Message - Al-Shamahy, Prof. Dr. Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2021)
Professor Dr. Jennifer Drambi Audu-Peter from University of Jos, Nigeria, with a charming smile and beauty, in Volume 6, Issue 1, January - February 2021; she explained what are the reasons for academics and researchers, choosing the right journal to publish their research results to the widest range of the public and expert vital to their success. These qualities were included in our beloved UJPR - and I would like to add that our beloved journal has achieved the ten goals of the sober medical journal, and these ten goals and main long-term tasks, so to speak, are “major challenges” for research in the field of pharmaceutical and medical informatics, including health informatics. This is the further development of information-processing methods and tools for: (1) Diagnosis (the "visual object"); (2) Treatment (“medical intervention with minimal pressure on the patient”); (3) Simulation therapy. (4) Early identification and prevention; (5) compensation for physical disabilities. (6) health counseling ("the informed patient"); (7) Health reports; (8) Health Care Information Systems. (9) Medical documentation and (10) comprehensive documentation of medical knowledge and knowledge-based decision support. So we believe that we are in the journal, already in progress. For all these goals and tasks, pharmaceutical, medical informatics can, and perhaps should, make significant contributions. If only what the journal presented during its career were listed, that the goal that it sought to achieve in general and its achievements so far, especially with regard to countries with little luck in the field of pharmaceutical and medical research, has been accomplished. In addition, some international researchers have described that some journals have turned into information laundering operations for the pharmaceutical industry. Pharmaceutical and medical journals have become a marketing machine in the first place, and we are also proud that our journal has deviated from this description. In conclusion, more perseverance for the advancement of our dear journal.